Pengaruh Persediaan Terhadap Peningkatan Profitabilitas Perusahaan - Wibowo, Elisabeth Maria; ., Iriyadi (Jurnal Ilmiah Akuntansi Kesatuan, 2014)
Inventory system provides an opportunity to improve productivity and eliminate costs that arefound to be necessary. Then, the company can overcome the waste-waste that has been happeningwith the use of traditional production systems. The purpose of this study was to determine impactinventory to stock and improved profitability Company X. This study was conducted with thesurvey directly on the object of research. This survey is intended for researchers will be able to betterinteract with the object interaktif in order to make it easier to understand the reality of the object ofstudy. Then from the data obtained during the survey along with the company's datadocumentation, will obtain a clear picture of who will facilitate researchers in solving the problemsthat occur in the company. The data analysis technique used is qualitative analysis techniques.This research result prove true that, by using the traditional systems it will be able to increase thecompany ' s profitability. It can be seen on the chapter 4 showing comparison of cost efficiencysupplies traditionally use policy. If cost and time can be minimized, then the company'sproductivity will be increased, the quality of the products is also increasing, with profitability.